Capaian Kemampuan Berpikir Reflektif Mahasiswa Peserta Mata Kuliah Akuntansi Manajemen Antar Semester - Trisye Natalia Kilay (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2018)
The purpose of study is to investigate empirically the differences in achievement of reflective thinking skills for management accounting courses between different semester students at the same time. There were 68 students of the Accounting Study Program at the Faculty of Economics, Darma Cendika Catholic University who took Management Accounting courses in the odd semester 2018/2019, which had filled out the research questionnaire, but only 66 questionnaires were feasible to be processed. The hypotehesis examined by using manova. Based on the results of quantitative data processing using SPSS, only reflections are seen different between semesters but this study failed to confirm the differences in habitual action, understanding, and critical reflection between semesters taking management accounting courses at the same time.